Field dependence of the magnetocaloric effect in core-shell nanoparticles - Franco, V.; Conde, A.; Sidhaye, Deepti; Bhagavatula L. V. Prasad; Poddar, P.; Srinath, S.; Phan, M. H.; Srikanth, H. (Journal of Applied Physics, 2010)
The field dependence of the magnetic entropy change peak at the low temperature surface spin freezing transition in chemically synthesized, monodispersed Co, Co-Ag, and Ni-Ag core-shell nanoparticles is studied, with the aim of gaining insight into the critical exponents of this transition. It is evidenced that although the magnitude of the peak entropy change and position of the peak can be tuned by changing the composition and nature (metallic or organic) of the shell and surfactant layers, the characteristics of the spin freezing transition are not altered. The field dependence of the refrigerant capacity also confirms this finding. (C) 2010 American Institute of Physics. [doi: 10.1063/1.3335514]

Large magnetocaloric effect, moment, and coercivity enhancement after coating Ni nanoparticles with Ag - Srinath, Sanyadanam; Poddar, Pankaj; Das, Raja; Sidhaye, Deepti; Bhagavatula L. V. Prasad; Gass, James; Srikanth, Hariharan (ChemPhysChem, 2014)
We observe a large magnetocaloric effect in monodisperse Ni and NicoreAgshell nanoparticles in the superparamagnetic region. The organically passivated Ni nanospheres show a large magnetic entropy change of 0.9 J kg(-1)K for a 3 T magnetic field change. In comparison to the surfactant-coated Ni nanoparticles, the NicoreAgshell nanoparticles show an enhanced coercivity, magnetization, and magnetocaloric effect (1.3 kgK for a 3 T magnetic field change). The coercivity at 10 K increases from 360 Oe for Ni nanoparticles to nearly 610 Oe for NicoreAgshell particles. This large enhancement is attributed to the enhanced inter-particle interaction, which is mediated by the metallic shell, over the relatively weaker dipolar interaction in the surfactant-coated Ni nanoparticles, and to modification of the surface spin structure.
Keywords: anisotropy; core-shell; magnetic properties; Nanoparticles; superparamagnetic